The effect of fertilizers, sowing time on phenological phases and productivity formation of winter rye in the Zauralye - M. S. Shmeleva (Зерновое хозяйство России)
The purpose of the current study was to identify patterns of the effect of doses, methods and terms of mineral fertilizing on the phenological phases and winter rye productivity in the Trans-Urals. The trial was conducted at the educational and production fruit and vegetable plot in 2021–2023. The object of the study was the winter rye variety ‘Pamyati Kunakbaeva’. Sowing was laid in weedfree fallow in two stages. During sowing, nitroammophoska was added in doses of 30, 60, 90 kg of active ingredient per ha. At booting stage, there was foliar feeding with 60 l of liquid complex fertilizers (N:P 11:37) per ha. The study results were processed according to B. A. Dospekhov’s methodology. There have been studied phenological phases of plants, yield structure parameters and productivity. The effect of the sowing period on phenological phases of plants under favorable weather conditions was established only in the autumn. Subsequently, there was no difference in the development of crops. In 2021/2022 there were obtained high yields in some variants at the first sowing date (N60P60K60, N60P60K60 + LCF NP11:37, N90P90K90 + LCF NP11:37). In 2022/2023, productivity was higher in the second sowing date variants. In general, over the two years of study, the most efficient was the application of the main fertilizer at a dose of 60 kg active ingredient per ha with the use of LCF. There have been established higher indicators for such yield structure elements as ‘number and weight of grains per ear’. The increase of these indicators in comparison with the control amounted to 8.7 and 0.4 g, respectively over the years of study. In 2021/2022 this variant showed the largest productivity (2.51 t/ha) and 1000-grain weight (41.2 g). In 2022/2023, the best indicators were identified in the variant N90P90K90 + LCF NP11:37, with 27.7 g of ‘1000-grain weight’ and 2.49 t/ha of productivity.